Impact of stratified resection margin classification on local tumor control and survival in patients with oral squamous cell carcinoma. Issue 8 (20th August 2021) - Hakim, Samer G.; von Bialy, Robert; Falougy, Mohamed; Steller, Daniel; Tharun, Lars; Rades, Dirk; Sieg, Peter; Alsharif, Ubai
Abstract: Background: Guidelines recommended for resection of oral cancer define a free margin of ≥5 mm as clear and safe (R0). This statement was questioned recently based on the assumption that different surgical margins may hold different risk categories. The aim of this study was to investigate the impact of stratification of the surgical margins on the survival outcome of patients with oral cancer. Methods: In a cohort of 753 patients, the hazard ratio for local recurrence‐free survival (LRFS), overall survival (OS), and oral cancer‐specific survival (OCSS) were estimated for R0 resection, the close margin of 1–4 mm, involved resection borders but with free frozen sections. Competing risk factors were considered in the statistical regression model. Results: One hundred seventy‐three (23%) patients developed local recurrence and 316 (42%) died in the 5 follow‐up years. There was a gradual improvement in the LRFS, OCSS, OS with the increase of clear margin. OS showed a similar tendency. Conclusion: Not all patients with an R0cm status carry the same risk for impaired LRFS, OCSS, and OS. Their risk to develop recurrence is higher than those patients with R0 ≥5 mm but stratified risk management can be recommended according to the presented results.